Self-Employed Immigrants in Denmark and Sweden : A Way to Economic Self-Reliance? - Pernilla Andersson; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2004)
Immigrants have a weak position in the labour market in most European countries. Many have difficulties in establishing themselves in the labour market, the employment rate is low and the hourly wages are generally lower than what could be expected from characteristics (age, gender, education). Many have to rely on the social transfer payments including social assistance. One way to avoid the problems in getting a job is to become self-employed. In this paper we make use of two large data-sets to study self-employment among immigrants in Denmark and Sweden. The three main issues covered are 1) if the immigrants are overrepresented among the self-employed, 2) the characteristics of self-employed immigrants, and 3) the incomes of the self-employed immigrants. In each case we compare the situation in the two countries. The immigrants, especially immigrants from non-Western countries, are overrepresented among the self-employed in both countries. The selfemployed immigrants in both countries have relatively low incomes, lower than natives with the corresponding characteristics.
Keywords: J23; J15; J61; 330; immigrant workers; self-employment; Migranten; Selbständige; Soziale Integration; Dänemark; Schweden